Ordering of neuronal apoptosis signaling: a superoxide burst precedes mitochondrial cytochrome c release in a growth factor deprivation model - Lieven, Christopher J. (2012)
Axonal injury to retinal ganglion cells, a defined central neuron, induces a burst of intracellular superoxide anion that precedes externalization of membrane phosphatidylserine and subsequent apoptotic cell death. Dismutation of superoxide prevents the signal and delays loss of these cells, consistent with superoxide being necessary for transduction of the axotomy signal. However, phosphatidylserine externalization is a relatively late step in apoptosis, and it is possible that the superoxide burst is not an early axotomy signal but rather a result of cytochrome c release from the mitochondrial inner membrane with consequent accumulation of reduced intermediates. Other possibilities are that both superoxide generation and cytochrome c release are induced in parallel by axotomy, or that cytochrome c release potentiates the effect of the superoxide burst. To distinguish these various possibilities, serum-deprived neuronal retinal cells were assayed in vitro for superoxide elevation and release of cytochrome c from mitochondria, and the distribution of these two markers across a large number of cells used to model the temporal ordering of events. Based on this model of factor-dependent cell death, superoxide precedes, and possibly potentiates, cytochrome c release, and thus the former is likely an early signal for certain types of neuronal apoptosis in the central nervous system.